2018
DOI: 10.1371/journal.pone.0202622
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of HIV-1 infection among men who have sex with men in Taiwan from 2013 to 2015

Abstract: Men who have sex with men (MSM) is the major risk population of HIV-1 infection in Taiwan, and its surveillance has become critical in HIV-1 prevention. We recruited MSM subjects from 17 high-risk venues and 4 community centers in northern and southern Taiwan for anonymous HIV-1 screening during 2013–2015. Blood samples were obtained for genotyping and phylogenetic analysis, and a questionnaire survey covering demographic variables and social behavior was conducted. In total, 4,675 subjects were enrolled, yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Methamphetamine is the prevalent recreational drug associated with "chemsex" in MSM 13 . A prior report in Taiwan showed that the proportions of methamphetamine use were 22.3% and 11.7% in HIV-positive and HIV-negative MSM, respectively 33 . Our study found that 16.0% of HIV-positive MSM had used methamphetamine in the prior three months, which was higher than the 7.8% of HIV-positive MSM in the United Kingdom 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Methamphetamine is the prevalent recreational drug associated with "chemsex" in MSM 13 . A prior report in Taiwan showed that the proportions of methamphetamine use were 22.3% and 11.7% in HIV-positive and HIV-negative MSM, respectively 33 . Our study found that 16.0% of HIV-positive MSM had used methamphetamine in the prior three months, which was higher than the 7.8% of HIV-positive MSM in the United Kingdom 34 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, the HIV-1 epidemic in Taiwan has primarily spread via sexual contact [24]. The subtype B and CRF01_AE are the cause of the majority of the infections (>90%) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Mean fluorescent densities were measured using the Image-Pro Plus program. Regarding the HIV-1 genotyping, the protocol was according to previous publication [24]. Briefly, the blood samples were drawn from the enrolled patients.…”
Section: Infectivity Hiv-1 Genotyping Assaysmentioning
confidence: 99%
“…In addition, four abstracts were selected based upon this review of references and all four were deemed eligible and their corresponding papers were included in the analysis. 15–18 Hence, 37 articles from 33 studies were included for the systematic review and meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We preferred using aORs with 95% CIs from the given publication, available for 28 studies. 14,1645 For five studies that did not report aORs, we used raw data to calculate the crude ORs and their 95% CIs. 15,4649…”
Section: Methodsmentioning
confidence: 99%